KEMAKSUMAN NABI: KAJIAN TERHADAP AYAT-AYAT ‘ITÂB TERHADAP NABI MUHAMMAD SAW - Sriwahyuni Sriwahyuni (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
This article aims to understand what the concept of the infallibility of prophets and messengers by seeing some interpretations of some verses contained in the Qoran are considered as ‘itâb (admonition/warning) for one of the prophets, he is the prophet Muhammad pbu. The data of this study was obtained through primary literature, it is an interpretation literature (kitab tafsir) of classic interpreter (mufassir) and some modern interpreters. This study was discussed in the descriptive-comparative analysis by using the infallibility (‘ismah )theory . Initially, the writer described admonition’s verses that will be studied by comparing it with two other interpretations, and then analyzed it. Thus it was found that interpreters differed in recognizing the exictence of admonition’s verses to the prophet Muhammad pbu in the Qoran. Finally, the study has analyzed and was found that the admonitions were not for a mistake or a sin that will eliminate the infallibility attribute that had attached to him, but it was as manifestations of the compassion of Allah to the Prophet in order to not too forces his self in preaching, because however he had do all the commands of Allah to convey all of his message or revelation.